GIS and the Digital Earth Labs - Sawada, Michael; Knudby, Anders; Richardson, Galen; Sauro, Claudia (Université d'Ottawa | University of Ottawa, 2023)
This resource was created as part of a project to develop open-access lab notes for the University of Ottawa's "GIS and the Digital Earth" (GEG2320) course and its French counterpart "SIG et la Terre numérique" (GEG2720). It contains lab notes for five labs with exercises for this introductory course, as well as the data needed for students to work through the labs. All labs are based on ArcGIS Pro, and require students to have access to this software. Follow this link to GitHub to download the data files: https://github.com/andersknudby/GEG2320
Keywords: Geographic information systems (GIS); Cartographic design; Modifiable areal unit problem; Coordinate systems and transformations; Geographic databases; Spatial analysis in vector; Remote sensing; Raster GIS; Open educational resource (OER)